Development of digital wind speed meter with wind direction - Mohd Mokhtar, Ismail (2007)
An aerovane is one of the devices that is used to measure wind speed and direction. The wind speed measured using aerovane is much more acurate as it measures the speed of the wind which parallel to the wind direction. This project mainly focuses on using microcontroller PIC 16F877A to control the circuit and building the aerovane type wind vane model. Hall Effect sensor is used for speed measurement and 10kΩ potentiometer for direction detection. The sensor resolution for speed measurement is one pulse per rotation. For direction, the specific direction is determined at every 45° rotation of potentiometer. The microcontroller is used as a central contoller to measure the speed and direction of the wind and displays it on a 16 x 2 characters LCD. From the measured pulse per minute, the speed is calibrated for displaying the value in km/h. While the direction will be display in specific direction which is North, NorthEast, East, SouthEast, South, SouthWest, West, and NorthWest. Based on the output, the PIC 16F877A can be an ideal microcontroller for developing this project. However, the aerovane modelling should be done in more accurate manner to get more accurate wind measurement. -Author